2019
DOI: 10.1111/cen.14123
|View full text |Cite
|
Sign up to set email alerts
|

Cabergoline may act as a radioprotective agent in Cushing's disease

Abstract: Context: Conventional fractionated radiotherapy (CRT) achieves control of pathological hypercortisolism in 75%-80% of patients with persistent or recurrent Cushing's disease (CD), over a mean period of 18-24 months. Medical therapy is recommended as bridge therapy while awaiting RT effect.Objective: To determine long-term outcome of CRT and its predictors in CD patients. Design, Setting and Patients:This is a retrospective case record analysis of 42 patients with CD who received CRT as a treatment modality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Radiotherapy is a valid therapeutic option, with median remission rates of 80% (123 patients in 7 studies), no recurrence rate and a median time to remission of 8 months [60]. However, cabergoline must not be used during radiotherapy, as it may increases recurrence rate due to a recently published study [61]. New hypopituitarism is a common problem in up to 38 [62]-40% of patients [63].…”
Section: Radiation Therapymentioning
confidence: 99%
“…Radiotherapy is a valid therapeutic option, with median remission rates of 80% (123 patients in 7 studies), no recurrence rate and a median time to remission of 8 months [60]. However, cabergoline must not be used during radiotherapy, as it may increases recurrence rate due to a recently published study [61]. New hypopituitarism is a common problem in up to 38 [62]-40% of patients [63].…”
Section: Radiation Therapymentioning
confidence: 99%
“…Sheehan et al observed that the remission was faster in the group in which medical therapy was withdrawn around the time of GKS [9]. Thakkar et al reported that remission was not affected in patients with cabergoline treatment in peri-radiotherapy period, but recurrence was found to be increased [51]. In our study, although the number of patients was small, especially in terms of cabergoline use, there was no significant difference in the rate of-and time to remission between patients using and those not using ketoconazole and/or cabergoline before RT.…”
Section: Gks N ( %)mentioning
confidence: 99%
“…Given the latency until post-RT remission, adjuvant medical therapy is needed to control hypercortisolism; periodic withdrawal allows cortisol secretion evaluation to assess treatment effect. 7 Although data are mixed on whether ketoconazole 246,249 or cabergoline 250 treatment at the time of SRS limits efficacy, they are often withheld temporarily at the time of RT. Hypopituitarism is the most common side effect of both conventional RT and SRS, seen in 25-50% of patients, and generally increases over time.…”
Section: Introductionmentioning
confidence: 99%